2023
DOI: 10.1186/s13098-023-01075-0
|View full text |Cite
|
Sign up to set email alerts
|

How effective are anthocyanins on healthy modification of cardiometabolic risk factors: a systematic review and meta-analysis

Abstract: Background In this meta-analysis, findings from recent studies on the preventive properties of anthocyanins (ACN) against cardiovascular disease are summarized. Methods MEDLINE, PubMed, Embase, Cochrane Library, and Google Scholar were searched and 2512 studies were found in a preliminary search. After screening of titles and abstracts, 47 studies met the inclusion criteria (randomized clinical trial design and sufficient data of outcomes). Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 88 publications
2
8
0
Order By: Relevance
“…Our findings indicate that a median dose of 320 mg/day anthocyanins for a period of 8 weeks significantly reduced the markers of glycemic control in individuals with T2DM including HbA 1c , FBG, and 2-h postprandial glucose level, with an absolute reduction of 0.31%, 0.63 mmol/L, and 1.6 mmol/L, respectively. This is supported by Neyestani et al ( 28 ), who claimed a significant reduction in FBG (0.85 mmol/L) after administrating anthocyanins in patients with T2DM and a decrease in HbA 1C (0.14%) in individuals with and without T2DM. Our findings were also consistent with that observed by a meta-analysis evaluating 32 studies performed with both healthy and cardiometabolic diseased populations on the effect of anthocyanins from fruit extracts or supplements.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our findings indicate that a median dose of 320 mg/day anthocyanins for a period of 8 weeks significantly reduced the markers of glycemic control in individuals with T2DM including HbA 1c , FBG, and 2-h postprandial glucose level, with an absolute reduction of 0.31%, 0.63 mmol/L, and 1.6 mmol/L, respectively. This is supported by Neyestani et al ( 28 ), who claimed a significant reduction in FBG (0.85 mmol/L) after administrating anthocyanins in patients with T2DM and a decrease in HbA 1C (0.14%) in individuals with and without T2DM. Our findings were also consistent with that observed by a meta-analysis evaluating 32 studies performed with both healthy and cardiometabolic diseased populations on the effect of anthocyanins from fruit extracts or supplements.…”
Section: Discussionsupporting
confidence: 52%
“…Yang et al ( 24 ) also indicated substantial improvements in lipid profile with the introduction of anthocyanins (from purified supplements and fruit extracts), including a reduction of TG, TC, and LDL cholesterol as well as an increase in HDL cholesterol levels in both healthy and cardiometabolic diseased populations. Similarly, Neyestani et al ( 28 ) reported a significant effect of anthocyanins on all lipid profiles in healthy adults and patients with different health conditions such as obesity, metabolic syndrome, hyperlipidemia, and T2DM. Tiwari et al ( 27 ) demonstrated a significant reduction in TC, TG, and LDL, but not in HDL in preclinical studies involving subjects who were overweight/obese, had pre-diabetes, and T2DM (human and animal).…”
Section: Discussionmentioning
confidence: 89%
“…A number of studies have confirmed the beneficial effects of anthocyanins on weight and BMI reduction [ 193 ]. Specifically, anthocyanin supplementation at ≤300 mg/day for 4 weeks has been shown to effectively reduce BMI and body weight [ 194 ]. Additionally, anthocyanins contained in Lycium ruthenicum Murray fruit counteracted obesity by inhibiting pancreatic lipase and regulating the intestinal microflora [ 176 ].…”
Section: The Effects Of Anthocyanins On the Prevention And Supportive...mentioning
confidence: 99%
“…Researchers have also assessed the effects of anthocyanins on body weight in humans. Numerous studies have shown that interventions with anthocyanins reduced BMI and body fat percentage [ 193 , 194 , 233 , 234 ]. In particular, anthocyanin supplementation at a dose of ≤300 mg/day for 4 weeks effectively reduced BMI and body weight [ 194 ].…”
Section: The Effects Of Anthocyanins On the Prevention And Supportive...mentioning
confidence: 99%
See 1 more Smart Citation